Experiences and attitudes related to newborn feeding in central Uganda: A qualitative study - Sewannonda, Andrew; Medel-Herrero, Alvaro; Nankabirwa, Victoria; Flaherman, Valerie J (Public Library of Science, 2022)
Objective Adequate infant nutrition is a critical cornerstone of population health, yet adherence to recommended breastfeeding practices is low in many countries in sub-Saharan Africa, including Uganda. This study aims to describe local attitudes, experiences and beliefs related to nutrition in early infancy in Central Uganda Design We conducted 5 focus group discussions and 12 key informant interviews to gather information on local attitudes, experiences and beliefs related to feeding in early infancy. Setting Urban areas of Central Uganda. Participants Parents and healthcare and public health professionals. Results Participants reported numerous concerns related to infant health including inadequate infant weight, premature birth, diarrhea, fever, gastrointestinal infection and malnutrition. Awareness of the infant health benefits of exclusive breastfeeding was prevalent but experienced as in balance with maternal factors that might lead to supplementation, including employment demands, physical appearance, pain, poverty and maternal health and malnutrition. Breastfeeding was highly valued, but use of unsafe breast milk supplements was common, including cow’s milk, black tea, glucose water, fruit juice, millet, maize, rice, potatoes, soy, sorghum, egg yolk, fish and ghee. Expression of breast milk was viewed as not consonant with local culture. Conclusions Participants were aware of the benefits of exclusive breastfeeding but described multiple barriers to achieving it. Supplementation with unsafe breastmilk supplements was considered to be more culturally consonant than milk expression and was reported to be the only affordable potential breast milk substitute for many families.
Keywords: Breast feeding, Breast milk, Infants, Uganda, Nutrition, Parenting behavior Child, health, Socioeconomic aspects of health